Proximal diabetic neuropathy presenting with respiratory weakness. Issue 4 (1st October 1999) - Brannagan, Thomas H; Promisloff, Robert A; McCluskey, Leo F; Mitz, Kathleen A
Abstract : A patient is described with proximal diabetic neuropathy presenting with respiratory weakness. A 50 year old man developed progressive shortness of breath over 2 months. He also had weakness of hip flexion. Phrenic nerve responses were absent, and spontaneous activity was seen in the intercostal and lumbar paraspinal muscles with long duration neurogenic MUPs and reduced recruitment in the diaphragm. Without treatment, the patient began to improve with resolution of his proximal leg weakness and breathing difficulties. Proximal diabetic neuropathy is another cause of neuromuscular respiratory weakness.